2022
DOI: 10.3389/fmed.2022.870391
|View full text |Cite
|
Sign up to set email alerts
|

Association between poor sleep quality and an increased risk of dry eye disease in patients with obstructive sleep apnea syndrome

Abstract: PurposeObstructive sleep apnea (OSA) is related to an increased incidence of dry eye disease (DED). However, their exact relationship is unknown and requires further well-designed studies with advanced mechanisms detection.Patients and methodsThis case–control study included 125 OSA cases and 125 age–gender-matched controls enrolled in the hospital between 1 January and 1 October 2021. OSA diagnosis and classification were performed using a polysomnography (PSG) assay. Detailed ophthalmological examinations, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 34 publications
3
2
0
Order By: Relevance
“…In our study, the OSDI scores in mild & moderate and severe OSAS groups were significantly higher ( p < 0.05) compared to the control group. Similar findings were reported in previous studies by Jian Sun et al ( 21 ), Qi Pu et al ( 22 ), and Mutlu Acar et al ( 9 ), who found that severe OSAS cases had high scores in OSDI questionnaire. Another study found a positive correlation between high OSDI scores and low TBUT ( 9 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In our study, the OSDI scores in mild & moderate and severe OSAS groups were significantly higher ( p < 0.05) compared to the control group. Similar findings were reported in previous studies by Jian Sun et al ( 21 ), Qi Pu et al ( 22 ), and Mutlu Acar et al ( 9 ), who found that severe OSAS cases had high scores in OSDI questionnaire. Another study found a positive correlation between high OSDI scores and low TBUT ( 9 ).…”
Section: Discussionsupporting
confidence: 91%
“…In a previous investigation of the sleep status and dry eye-related risks of OSAS patients, the oxford corneal staining score was higher in OSAS patients with poor sleep quality than those with good sleep quality, with significant staining differences observable between the two groups. Though not the same as our observation index, i.e., corneal fluorescence staining, both measures indicate the ocular surface health of patients (22). Wu et al (30) also reported significant CFS differences between dry eye patients and controls, with higher scores of dry eye patients as compared to the control group, which supports the findings of our study.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations